2017
DOI: 10.1021/acssuschemeng.7b00954
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cleavage of Strong Hydrogen Bonds in Cotton by Deep Eutectic Solvents and Facile Fabrication of Cellulose Nanocrystals in High Yields

Abstract: The content of cellulose in biomass is important for producing nanocellulose in high yields. Cotton fibers containing ultrahigh purity (∼95%) cellulose are ideal feedstock for nanocellulose production. However, the presence of strong hydrogen bonding between the cellulose chains limits the use of cotton fibers for the production of nanocellulose in a facile and mild process. Here, efficient cleavage of the strong hydrogen bonds in cotton and ultrafast fabrication of cellulose nanocrystals (CNCs) with a high yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(118 citation statements)
references
References 36 publications
8
105
0
Order By: Relevance
“…In addition, previously significant decrease in the DP has been observed when cellulose treated with acidic DES (Sirviö et al 2016). Although hydrolysis of cellulose during the chemical modification prior CNFs production can help the mechanical fibrillation and thus liberation of nanosized cellulose, it is not prerequisite, as it has been previously reported that even use of non-hydrolytic DES can help the nanofibrillation of natural fibers (Sirviö et al 2015c;Liu et al 2017). It should be noted that due to the significant chemical modification of cellulose with DES, the DP values calculated be limiting viscosity method should taken more as guideline than an absolute values.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, previously significant decrease in the DP has been observed when cellulose treated with acidic DES (Sirviö et al 2016). Although hydrolysis of cellulose during the chemical modification prior CNFs production can help the mechanical fibrillation and thus liberation of nanosized cellulose, it is not prerequisite, as it has been previously reported that even use of non-hydrolytic DES can help the nanofibrillation of natural fibers (Sirviö et al 2015c;Liu et al 2017). It should be noted that due to the significant chemical modification of cellulose with DES, the DP values calculated be limiting viscosity method should taken more as guideline than an absolute values.…”
Section: Resultsmentioning
confidence: 97%
“…DESs have been studied as solvents (Gutiérrez et al 2010;Zdanowicz et al 2016), reagents (Azizi and Alipour 2015), and catalysts (Wang et al 2015) in organic synthesis and biomass treatment. Recently, a number of studies have emerged in which DESs are used as a solvent for cellulose derivatization (Abbott et al 2005(Abbott et al , 2006Park et al 2013;Willberg-Keyriläinen et al 2017) and for the production of various types of nanocelluloses (Sirviö et al 2015c(Sirviö et al , 2016Selkälä et al 2016;Hosseinmardi et al 2017;Liu et al 2017). A reactive DES has also been demonstrated in production of a derivatized, alkaline-soluble cellulose (Sirviö and Heiskanen 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Then the anionic CNFs could be obtained through the followed microfluidization of carboxylated ground wood pulp. A microwave-assisted DES pretreatment method for fast CNCs production was proposed by Liu and coworkers [235]. It took only a little time (not more than 3 min) for the pretreatment of cotton, and then a high-intensity ultrasonication process was adopted.…”
Section: Deep Eutectic Solvent Pretreatmentsmentioning
confidence: 99%
“…25,26 Recently, DESs have been utilized in the production of CNFs [27][28][29][30] and CNCs. 31,32 In this study, a DES based on guanidine hydrochloride and anhydrous phosphoric acid was used to dissolve cellulose at room temperature. Dissolving pulp and microcrystalline cellulose were studied as cellulose sources.…”
Section: Introductionmentioning
confidence: 99%